A review of the carotid artery and facial nerve canal systems in extant turtles - Rollot, Yann; Evers, Serjoscha W.; Joyce, Walter G. (PeerJ, 2021)
The cranial circulation and innervation systems of turtles have been studied for more than two centuries and extensively used to understand turtle systematics. Although a significant number of studies related to these structures exists, a broader comprehension of variation across the tree has been hindered by poor sampling and a lack of synthetic studies that addressed both systems together. We here provide new insights regarding the carotid circulation and facial nerve innervation systems in a broad set of extant turtles using CT (computed tomography) scans, which allow us to trace the canals these structures form in bone and understand the interaction between both systems. We document that the palatine artery, including the lateral carotid canal, is absent in all pleurodires and carettochelyids and was likely reduced or lost several times independently within Testudinoidea. We also highlight osteological correlates for the location of the mandibular artery. We finally summarize variation regarding the placement of the mandibular artery, location of the geniculate ganglion, placement of the hyomandibular and vidian nerves, and situations where we recommend caution when assessing canals in fossils. A morphometric study confirms that the relative sizes of the carotid canals are correlated with one another. Our results have the potential for building new phylogenetic characters and investigating the circulation systems of fossil taxa, which are expected to shed light on the evolution of the circulation system of turtles and clarify some unresolved relationships between fossil turtle clades.
Keywords: Testudines; Carotid artery; Facial nerve; Interspecific variation